CaMKII-dependent regulation of cardiac Na+ homeostasis - Grandi, Eleonora; Herren, Anthony W. (Frontiers in Pharmacology, 2014)
Na+ homeostasis is a key regulator of cardiac excitation and contraction. The cardiac voltage-gated Na+ channel, NaV1.5, critically controls cell excitability, and altered channel gating has been implicated in both inherited and acquired arrhythmias. Ca2+/calmodulin-dependent protein kinase II (CaMKII), a serine/threonine kinase important in cardiac physiology and disease, phosphorylates NaV1.5 at multiple sites within the first intracellular linker loop to regulate channel gating. Although CaMKII sites on the channel have been identified (S516, T594, S571), the relative role of each of these phospho-sites in channel gating properties remains unclear, whereby both loss-of-function (reduced availability) and gain-of-function (late Na+ current, INaL) effects have been reported. Our review highlights investigating the complex multi-site phospho-regulation of NaV1.5 gating is crucial to understanding the genesis of acquired arrhythmias in heart failure (HF) and CaMKII activated conditions. In addition, the increased Na+ influx accompanying INaL may also indirectly contribute to arrhythmia by promoting Ca2+ overload. While the precise mechanisms of Na+ loading during HF remain unclear, and quantitative analyses of the contribution of INaL are lacking, disrupted Na+ homeostasis is a consistent feature of HF. Computational and experimental observations suggest that both increased diastolic Na+ influx and action potential prolongation due to systolic INaL contribute to disruption of Ca2+ handling in failing hearts. Furthermore, simulations reveal a synergistic interaction between perturbed Na+ fluxes and CaMKII, and confirm recent experimental findings of an arrhythmogenic feedback loop, whereby CaMKII activation is at once a cause and a consequence of Na+ loading.